Ikhtiartu Lajnati Bahsi Al Masail Al Fiqhiyyah Fi Muqorrarat Mutamarat Nahdati Al-Ulma' Min Sanah 1926 - 2010 Fi Bab Al_janaiz (Dirasatun Tahlilyyatun Naqdiyyatun - Yahya, Yahya (2016)
This research focuses on the fiqh selection of Bahṡu al-Masā'il in ahkam fuqoha book. It is a collection of decisions made by Muslim scholars in their conference since 1926-2010 which belongs to the discussion of Janāiz and method of istimbāṭ used by Bahṡu al-Masā'il. The objectives of this research are to describe about ikhtiyarat lajnah Bahsi al-Masā'il, and to describe method that becomes the base of its law. This is a descriptive qualitative research. The methods used in this research are historical approach and uṣul al-fiqh. The findings of this research showed that Bahṡu al-Masā'il used the whole method; however, it often used Manhaj Qauly. Bahṡu al-Masā'il tends to refer to Syafi'i's school. This activity of Bahṡu al-Masā'il was held as substitute of ijtihād which in Islam known as the seriousness of mujtahid in making Islamic law from the detailed Islamic argumentations. The characters of fiqh selection of Bahṡu al-Masā'il are consistent in using method of Istimbāṭ made by Nahdlatul Ulama, using argumentations based on al-Qur'an and Hadis, the opinions of fiqh experts are from Syafi'i's school, using Qiyās and considering the problems, customs, as well as easy. Based on the research findings, there are nine things that become the focus of discussion: the understanding of lajnah toward the meaning of ijtihād and the activity to substitute it, fiqh knowledge as the king of knowledge, the way of following the school, the understanding of lajnah toward the meaning of Ahlu al-sunnah wa al-jamā'ah, domination of great Muslim scholars, the interpretation of kullu bid'atin ḍalālah, the attitude towards what prophet Muhammad didn't do, the use of Qiyās in worship, and the attention to customs and rules of collective ijtihād.